(untitled) (Prostor, 2023)
The article explores the process of central planning development and dome-bearing systems analysis in mosques belonging to Classical Ottoman Architecture, focusing on the typological plan variations found in Sinan the Architect’s octagonal-based central domes. It is aimed to determine the spatial typology of these octagonal based central domes, as they play a crucial role in creating a central space in mosques. The typology studies focused on the load-bearing systems in central dome designs of eighteen surviving mosques designed by Sinan the Architect. The study method involves scanning scientific publications, state archives, and photographing mosques. Mosques ground floor plans, including their dome projections and sectional drawings, have been examined. Gathering all the data from analysing the transfer of the dome load enabled a categorisation of eighteen mosques that can be classified into two primary groups and three sub-groups within each group.